Isha-Upanishad and Economics Consideration: An Elucidation - Gewali, Babu Ram (Economic Literature, 2016)
In this article, the effort has been made to trace the tradition of oriental economic thoughts- spread in the four Vedas and Upanishad, which are the earliest documents of human civilization. For the analysis the first Upanishad- Isha has been selected. This analysis is based on the first mantra of Isha-Upanishad. It is concluded that the first serious econic thinking was inisitated by the composer of Upanishad. Economic Literature, Vol. XI (35-39), June 2013